Salicylic acid, temperature and storage periods in the conservation of gladiolus floral stems from the organic no-till system - Negrelli, Welton Schiles; Lima, Claudia Simone Madruga; Leandrini, Josimeire Aparecida; Oliveira, Rivael de Jesus; Baldin, Katia Birgeier (Revista de Ciências Agroveterinárias, 2023)
The post-harvest characteristics of agricultural products are influenced by several factors such as the cultivar, environmental conditions, cultural practices, and production systems. Post-harvest conservation is one of the challenges of the cut flower production chain. Thus, the objective was to evaluate salicylic acid concentrations, temperature and storage periods in the conservation of gladiolus floral stems from the organic no-tillage system. The work was carried out at the Federal University of Fronteira Sul - Campus Laranjeiras do Sul-PR. Stems of gladiolus cultivar Yester, coming from cultivation with presence and absence of ground cover were used. For this research, two experiments were carried out. The first consists of a completely randomized experimental design, in a three-factor scheme (soil cover (2) x storage temperature (2) x storage period (9)). With and without cover, at two storage temperatures (5°C) ± 2°C) and (20 ± 2°C), in storage periods from 0 to 16 days. The second experiment has a completely randomized design, in a three-factor scheme (salicylic acid concentrations (5) x (storage temperatures (2) x storage period (10)). 0, 1.5, and 2.0 mM salicylic acid at two storage temperatures (5°C) ± 2°C) and (20 ± 2°C), in storage periods from 0 to 18 days. The evaluations made were: caterpillar attack, stem diameter, stem tortuosity, basal-apical bud length, number of open florets rand number of senescent florets. For both experiments, the treatments influenced the responses of a number of open florets and number of senescent florets. The use of salicylic acid at a concentration of 0.5 Mm associated with refrigerated temperature and floral stems from the cover crop system provide an extension of the conservation of gladiolus floral stems.